The Bourbon project of a Jewish Naples between the anxiety of renewal and a return to the past: Peer reviewed article (Italian Review of Legal History, 2021)
In Naples, since the early sixteenth century, a set of measures, characterized by variously afflictive contents, regulated the legal status of the Jews who had settled, also thanks to the protection offered to them by the Aragonese kings, in the southern part of the peninsula. The succession of these provisions testifies to the centrality of the Jewish theme in the complex balance of political, religious and economic relations but, at the same time, reveals the evident difficulty of finding a decisive answer to a question that, precisely by those forces, was constantly influenced. The outcome of this dynamism determined, over the centuries, the oscillation between admitting, although with different limitations, the settlement of the Jewish community and the need to decree its expulsion. Between the two poles, there was the imposition of various limitations including the obligation to wear the “sign”.Compared to these precedents, the edict about the readmission of the Jews, published in February 1740 by Charles of Bourbon, marked an epochal turning point. The objective pursued by the Bourbon government was not only to provide a base of support for commercial exchanges, but rather to create favourable conditions for the arrival and settlement of the Israelite community. At the basis of that edict there was the design of a Jewish Naples: a city capable not only of welcoming the Jewish community and allowing its peaceful establishment, but, above all, able to adopt the commercial and productive mentality of the Jews. That intellectual osmosis would have renewed the Kingdom.Guaranteed by immunities and privileges, the Jews would have settled in Naples as had happened in Livorno, thanks to the so called Livornine. In Livorno, the Jews had become a very important component in the economic and political equilibrium. Thanks to the favourable initiatives taken by Ferdinando I de’ Medici, the Israelite community had grown strong and prestigious and this had translated into an advantage for the overall economy. From a legal point of view, the Livornine became the archetype to be inspired by. This is confirmed by the frequent citation of the Livorno model in the eighteenth-century sources concerning the kingdom of Naples. What happened in that city was the most effective term of comparison to demonstrate, against all prejudices, the usefulness of the Jews’ peaceful settlementA mercantilist vision pushed to consider the Jewish presence absolutely required. So it was necessary to overcome the widespread prejudices against a community of infidels and usurers. Adopted after a long and problematic debate, the Bourbon project required an act of courage. Thanks to it, the reformers carried out a regulatory intervention of sure innovation, but, above all, they showed, free from the interference of the Court of Rome, the ability and the strength to decide their own regulatory framework.The reform did not represent a sectoral intervention, but it was part of a more complex legal plan aimed at cultivating human society. In this horizon, several sources record the link between that initiative and the contemporary institution of the Supreme Magistrate of Commerce. Launched in the space of a few months, both reforms were the result of the synergy between modern intellectuals and the governmental policy prevalent in the early years of the Bourbon kingdom. Any way the parallelism existing between the two historical events and their developments remarks an important change in the Charles’ government. Both events followed a trend that, in time and manner, was comparable. While developing within this common horizon, the Jewish affair was marked by undeniablespecificities deriving from its political-religious implications. The tensions with the Church of Rome, already after the adoption of the edict, acted over time, tearing the basis of consensus for the reform. The effect was the gradual prevailing of a new prudent line ofcaution, that faithfully reflected the change taking place in the Court of Charles. The progressive weakening of the Secretary of State José Joaquín de Montealegre and his definitive departure in 1746 radically changed the juridical-political horizon. In July 1747, the expulsion of the Jews from the Kingdom marked the decline of reformist actions.
Keywords: Jews; Charles of Bourbon; Supreme Magistrate of Commerce; infidels; ghetto